Synthetic Approaches to Acyl Hydrazides and Their Use as Synthons in Organic Synthesis - Spiliopoulou, Nikoleta; Constantinou, Constantinos T.; Triandafillidi, Ierasia; Kokotos, Christoforos G. (Synthesis, 2020)
Acyl hydrazides constitute very important moieties in organic chemistry and have been employed as starting materials for different transformations to many classes of organic compounds. In this review, at first the approaches towards the synthesis of acyl hydrazides are presented. Furthermore, in the second part, the uses of this skeleton as an important intermediate for the synthesis of useful organic compounds are analyzed.1 Introduction2 Approaches towards the Synthesis of Acyl Hydrazides2.1 Synthesis of Acyl Hydrazides from Aldehydes2.2 Synthesis of Acyl Hydrazides from Carboxylic Acid Derivatives3 Acyl Hydrazides as Useful Synthons in Synthetic Organic Transfor mations3.1 Acyl Hydrazides as Synthetic Precursors for the Synthesis of Car bonyl Compounds3.2 Acyl Hydrazides as Synthetic Precursors for the Synthesis of Het erocyclic Rings4 Conclusion
Keywords: acyl hydrazides; aldehydes; azodicarboxylates; synthons; intermediates